Non-standard patch test - Adelia, Astri; Budianti, Windy Keumala; Marissa, Melani; Effendi, Evita Halim (UI Scholars Hub, 2018)
In managing contact dermatitis, identification of the causative agent is essential to prevent recurrent complaints. Patch test is the gold standard to identify the causative agent. Nowadays, there are many patch test standard materials available in the market, but do not include all the materials that potentially cause contact dermatitis. Patch test using patient’s own products or later we refer to as non-standard materials, is very helpful in identifying the causative agents of contact dermatitis. Guidance is needed in producing non-standard patch test materials in order to avoid test results discrepancy.